Dilema Desainer: Keresahan dan Pragmatisme dalam Persepsi Publik akan AI Generatif dalam Industri Kreatif Indonesia - Wiradarmo, Aulia Ardista (Fakultas Seni Rupa dan Desain ITB, 2025)
The rise of generative AI presents a dilemma due to the public’s pragmatic acceptance of AI-generated design works (M=5.33, SD=1.89), alluding to the possibility of creative labor displacement. Grounded in Christensen’s Innovator’s Dilemma and Mori’s Uncanny Valley, this study examines how the Indonesian public perceives the ethical and utilitarian tensions of AI adoption. Using a sequential explanatory mixed-methods approach, an online survey (n=553) was conducted with respondents aged 20 to 50 in 10 Indonesian cities. Participants evaluated four case studies—advertisement, book cover, Instagram post, and photo manipulation—alongside their general sentiments. Findings indicate lower acceptance of GenAI for commercial (M=4.78, SD=1.84) than for personal use (M=5.43, SD=1.58), and concerns about GenAI’s potential to replace designers (M=5.2, SD=1.70). The lowest receptivity was observed in video and photo manipulation, reflecting the uncanny valley effect. Meanwhile, respondents tend to justify the use of GenAI when there are no formal regulations, thereby diminishing their ethical concerns, while also exhibiting difficulties in identifying AI-generated images. These perceptions underscore the importance of AI governance in protecting human designers from being replaced by machines and ensuring the authenticity of design works.